Effect of Freezing Time on the Nutritional Value of Mystus gulio (Nuna tengra), Mystus tengra (Bazari tengra) and Mystus cavasius (Ghulsha tengra) (Journal of Science Foundation, 2013)
Three different species of tengra; Nuna tengra (Mystus gulio), Bazri tengra (Mystus tengara), Gholsha tengra (Mystus cavasius) were kept in freezing condition for 20 days to investigate the effect of freezing (-5°C) time on the nutrient composition (protein, lipid, moisture). The average weight of the sample was 46.5gm, 23.94gm, and 15.48gm for Nuna tengra, Gholsha tengra and Bazri tengra respectively. Samples were collected from Gollamari, Khulna. The amount of protein and lipid reduced while amount of moisture increased with prolongation of freezing time. The amount of moisture for Mystus tengara, Mystus cavasius, Mystus gulio increased from 76.12% to78.02%, 75.35% to 77.25%and 76.03% to 78.23% respectively. At fresh condition the protein content of Mystus tengara, Mystus cavasius, Mystus gulio were 16.26%, 15.52% and 14.80% and at the end of the experiment protein were 14.97%, 13.91% and 13.43%. At fresh condition the lipid content of Mystus tengara, Mystus cavasius, Mystus gulio were 6.15%, 5.98% and 6.20% and after twenty days of its freezing the observed lipid content were 4.9%, 5.37% and 4.86%. However, at the end of the study, no significant (p>0.5) difference was observed among different nutrient level due to increasing freezing time. DOI: http://dx.doi.org/10.3329/jsf.v8i1-2.14634 J. Sci. Foundation, 8(1&2): 119-122, June-December 2010